Seismicity in Central America (1520–2020) and earthquake catalog compilation for seismic hazard assessments - Gamboa Canté, Carlos José (2024)
Central America is a seismically active region located in a tectonic setting dominated by the subduction zone between the Cocos and Caribbean plates, transform boundaries between the North American and Caribbean plates, and local or crustal faulting with some of the most important fault systems aligned with the volcanic arc. Combining seismic data from various Central American seismic agency catalogs covering the period from 1520 to 2020, we present an updated regional earthquake catalog for the region. Fourteen databases containing seismic events from local and regional agencies were collected for different time periods, homogenized to moment magnitude (Mw), and subsequently unified using a prioritization criteria approach. We analyzed to the data to identify and remove duplicate earthquakes, prioritizing records with the lowest RMS value, depth consistent with their location based on the region’s crustal thickness, and magnitudes in accordance with historical reports or bibliographic sources. Additionally, significant seismic events (Mw ≥ 6.0) were carefully reviewed based on their epicentral locations and magnitudes, according on reliable publications. The earthquake catalog compiled includes a total of 260 548 earthquakes, for which we conducted a descriptive, spatiotemporal statistical analysis, as well as estimations of the magnitude of completeness (Mc) and declustering. Among the most important results, we highlight recent completeness periods for magnitudes Mw < 5.0. Geographically, seismic zones with better Mc are directly related to either good seismic network coverage or high seismicity rates in the region. As regards declustering, the Reasenberg declustering method considers several main shocks with ~ 76% of the earthquakes compared to the initial catalog and the Uhrhammer method considers ~ 51% as main shocks.